Keanekaragaman dan perilaku menggigit nyamuk sebagai vektor potensial filariasis di Kabupaten Banyuasin, Sumatera Selatan - Rini Pratiwi; Chairil Anwar; Salni Salni; Hermansyah Hermansyah; Novrikasari Novrikasari (Jurnal Entomologi Indonesia, 2019)
Filariasis is a chronic infectious disease caused by filarial worms and transmitted by various types of mosquitoes such as Mansonia, Anopheles, Culex, Aedes, and Armigeres. This study aims to determine the diversity and biting behavior of mosquito species as the potential vector of filariasis transmission in Banyuasin Regency, South Sumatera. The research was conducted for 12 hours from 18.00 to 06.00 with human landing collection method and animal biting trap in December 2016. The results showed that the mosquito diversity in the studied area was high with 16 species of mosquitoes successfully identified in which Ma. uniformis (47.28%), Cx. tritaeniorhynchus (23.89%) and Cx. vishnui (14.48%) were the most dominant mosquitoes collected. The result also showed that the biting behaviour of Ma. uniformis was found to be more active outdoors than indoor with man biting rate (MBR) of 100,50 mosquitoes per night and man hour density (MHD) of 11,90 which was the highest of all captured species. Further parity rate analysis supported the collecting result by showing the estimated age of Ma. uniformis population which was 31.8 days and positively confirmed M. uniformis as a vector of filariasis transmission